PREVALENCE AND RISK FACTORS ASSOCIATED WITH HEPATITIS B VIRUS INFECTION AMONG ONCOLOGY PATIENTS - Almohya, Gameel Ahmed Mohammed; El-Zine, Monya Abdullah Yahya; Al-Shamahy, Hassan Abdulwahab; Al-Madhaji, Anowar Gasem; Assayaghi, Rowa Mohammed (Universal Journal of Pharmaceutical Research, 2025)
Background and aims: Hepatitis B virus (HBV) screening for patients with newly diagnosed solid cancer is not standard practice in oncology, and authorities disagree on whether complete screening should be carried out. Additionally, research on the risk factors for HBV infection in this patient population may differ from that in the general population. Therefore, estimating the prevalence of HBV and risk factors for HBV infection in individuals with recently diagnosed solid cancer was the study’s goal. Subjects and methods: Newly diagnosed cancer patients at the oncology center of Al-Jumhori Hospital in Sana’a, are included in this cross-sectional study. A regular questionnaire created specifically for this study was used to gather data, which included demographic information, risk factors, cancer type, and test findings. Using an ELISA assays for HB surface antigen and HB Core IgG anti-antibodies were conducted. Results: The study analyzed 300 cancer patients with HBV testing, with a mean age of 42.9 years and a sex distribution of 37.6% men and 62.4% women. The crude HBV prevalence was 5%, with females having a higher prevalence. The study found no significant association between age, rural residency, married status, blood transfusion frequency, or blood sources with HBV risk. No association was found between under treatment chemotherapy and HBV infection. Conclusions: This study examines the frequency of HBV infections in patients with solid tumors for the first time in Yemen. Our study found that the nationwide prevalence of HBV was higher in cancer patients than in the broad population. Peer Review History: Received 15 October 2024; Reviewed 7 November; Accepted 21 December; Available online 15 January 2025 Academic Editor: Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Reviewers: Dr. Sheikh Abdul Khaliq, Department of Pharmacy Practice, Faculty of Pharmacy, Hamdard University, Karachi, Pakistan, drwadhsheikh1974@gmail.com Dr. Taiwo O Elufioye, University of Ibadan, Nigeria, toonitaiwo@yahoo.com